Laser welding thermal analysis of 20mm-thick EH40 steel with gap through an equivalent thermal conductivity method - Guolong Zhang; Yu Huang; Xuanrui Liu; Hui Wang; Youmin Rong; Yifan Peng; Jiajun Xu (Journal of Advanced Joining Processes)
Laser welding of thick plates is extremely sensitive to the gap between joints. With the same laser welding parameters, slight adjustment of the gap can lead to different weld morphologies. An appropriate joint gap is conducive to increasing the penetration depth and reducing defects. To investigate the influence of the gap between butt joints on the penetration depth during single-pass laser welding of 20 mm thick EH40 steel, five groups of experiments were conducted with a laser power of 15 kW and a welding speed of 10mm/s, and gap sizes ranging from 0 to 0 .4mm. A finite element model of the temperature field was established for the experimental samples. Using the concept of equivalent substitution, the heat transfer process was used to replace the downward flow of the molten pool along the gap, and the equivalent thermal conductivity was derived to predict the penetration depth under different gap sizes. The results showed that within the gap range of 0–0.3 mm, the penetration depth increased and spatter decreased as the gap increased. When the gap exceeded 0.2 mm, weld depression began to appear. The maximum penetration depth of 19.33 mm was achieved when the gap was 0 .3mm. When the gap reached 0.4 mm, unacceptable severe collapse occurred in the weld. Additionally, the accuracy of the temperature field simulation results was verified by the experimental results.